Revolutionizing Electric Utilities: The Transformative Potential of Blockchain Technology - Rajesh Kolli (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the transformative potential of blockchain technology in the electric utility industry, a sector valued at 2.4 trillion globally. It examines how blockchain addresses critical challenges in grid management, renewable energy integration, customer engagement, and security. The study highlights blockchain’s ability to enhance operational efficiency, facilitate peer-to-peer energy trading, improve customer satisfaction, and reduce fraud. Key benefits include potential grid efficiency improvements of up to 30%, increased local renewable energy consumption by 35-40%, and significant reductions in billing errors and customer complaints. Despite challenges such as high infrastructure costs, regulatory hurdles, and scalability concerns, the blockchain in energy market is projected to reach 34.7 billion by 2029, with experts predicting it will play a crucial role in shaping the future of utilities. The article provides a comprehensive overview of blockchain’s applications, benefits, and challenges in the utility sector, supported by industry data and expert predictions.